Effect of Carp Glycophorin as an Antibiotic Reagent: Application of Carp Glycophorin from Red Blood Cell (RBC) Membranes as an Antibiotic Reagent - Aoki, Takahiko; Kurimoto, Takeshi; Inoue, Taisuke; Sugiura, Hikaru (European Journal of Applied Sciences, 2023)
Carp red blood cell (RBC) membranes contain a glycophorin (GP) that is responsive to a carp pathogen. The efficacy of carp GP as an antibacterial reagent was evaluated for the control of disease in rainbow trout (Oncorhynchus mykiss). The results suggest that intravenous administration of GP significantly delays the time of death following challenge with Vibrio anguillarum. In addition, we showed that carp GP was effective at adsorbing V. anguillarum and Micrococcus luteus from suspension following GP-binding column chromatography. After conducting small column experiments, we performed an upscaling column attached to a 500 L water tub with Escherichia coli.